Humibacter albus gen. nov., sp. nov., isolated from sewage sludge compost - Vaz-Moreira, Ivone (2011)
A bacterial strain isolated from sewage sludge compost, strain SC-083T, was characterized. The isolate was a motile, Gram-positive, short rod, forming coryneform V-shaped cells during the early stages of growth. The organism was strictly aerobic and able to grow between 22 and 36 °C and between pH 5.5 and 8.0. The predominant fatty acids were cyclohexyl-C17 : 0, anteiso-C17 : 0 and iso-C16 : 0, the major respiratory quinones were menaquinone 11 (MK-11) and 12 (MK-12), and the genomic DNA G+C content was 68 mol%. The peptidoglycan contained the diagnostic diamino acids ornithine and 2,4-diaminobutyric acid and was of acetyl type. The 16S rRNA gene sequence analysis indicated that this isolate belongs to the family Microbacteriaceae with the type strains of the species Leifsonia xyli (96 % gene sequence similarity), Leifsonia shinshuensis (96 %), Leifsonia naganoensis (95 %), Leifsonia aquatica (95 %), Agromyces ramosus (95 %) and Curtobacterium citreum (95 %) among the closest phylogenetic neighbours. The phylogenetic analysis and phenetic characteristics support the proposal of a new genus and a novel species, with the name Humibacter albus gen. nov., sp. nov. The type strain of Humibacter albus is SC-083T (=DSM 18994T =CCUG 54538T =LMG 23996T)